Influence of Teachers‟ Preparedness on English Curriculum Implementation in Kenyan Schools (Asian Education Studies, 2023)
The Government of Kenya (GoK) touts teacher-preparedness as a critical factor that shows the equipping of aprofessional teacher for quality performance and satisfactory learner performance in national examinations.Despite the efforts by the GoK, there is a worrying trend of students completing school with reading and writingdifficulties. The Kenya National Examinations Council (2020) contends students‟ poor performance in Englishfor the past 5 years, falling short of the average mean of 50%. Descriptive research design was used. A sample of44 principals, 88 teachers and 345 form three students across 50 public secondary schools in Kakamega North,were targeted. A questionnaire, interview schedule, classroom practice observation schedule, and focus groupdiscussion guide were used to collect data. Qualitative data was analyzed thematically whereas quantitative datawas presented through tables, percentages and frequencies. Chi-square test was performed to test hypothesis.Response rate was 79.5%. The findings indicated that majority (97.1%) of the teachers participated incoursebooks and other revision textbook in-service courses as per the changing trends in teaching of Englishwhereas ICT workshops had low percentages, a gap pointing on teacher level of preparedness. The findings fromprincipals indicated, teachers of English sometimes declined to take up ICT in-service trainings for fear ofadditional responsibilities in school. Findings from FGDs show, teachers were rated average by most students interms of preparedness in material use in classrooms. On determining the extent to which teacher level ofpreparedness influence implementation of English curriculum in school, teachers‟ opinions had a Mean of4.0000; Standard deviation of 3.08338; and Skewness of .397, indicating teacher level of preparedness has a highand strong positive influence on implementation of English curriculum in school if well checked and applied.The study established a significant relationship between teacher level of preparedness and implementation ofEnglish curriculum (p=0.007